A análise do risco morte à luz da Convenção n. 102 da Organização Internacional do Trabalho - Queiroz, Vera Maria Corrêa (2018)
The purpose if this work is to study and analyze the social death risk in the light of Convention n. 102 of the International Labor Organization - ILO, within the Social Law concentration area which addresses the Minimum Standards of Social Security, including the forms implemented in Brazil in view of the benefit of Pension for Death in the General Social Security System. Its development starts from a historical context of social protection and Social Security, and especially the social security subsystem, based on research of doctrine, legislation and jurisprudence, raising relevant issues within the context approach, with necessary delimitations in the research's object in view of the purpose for which the theme is available. The methodological design is clarified in detail throughout the social security benefit study's development, in order to establish the scientific research of the law in relation to social law. A comparative advantage is sought in other legal systems of the signatory countries of the international standard under analysis